THE INFLUENCE OF DILATATION DUE TO EARTHQUAKE LOADS ON HIGH-RISE STRUCTURES WITH AN H-SHAPED FLOOR PLAN - Mujib, Sahrul; Budiman, Budiman; Hanif, Basit Al (International Journal of Civil Engineering and Infrastructure, 2024)
Earthquakes are one of the factors in the collapse of a building structure because vibrations cause movement in the building structure above it, building structures with asymmetrical shapes tend to experience displacement or movement of structural elements higher than structures with symmetrical shapes, asymmetrical building shapes, for example, such as U, L, T and H-shaped building plans with the dilatation method aiming to separate the building to be simpler and make the building more symmetrical. In the analysis of the building structure, 5 models are modeled, a model without dilation (H-shaped plan), a two-column dilation model 1A, a two-column dilation model 1B, a cantilever dilation model 1A and a cantilever dilation model 1B. The results of the structural analysis with the two-column dilation and cantilever dilation methods affect the value of the structural period, the deviation between floors and the p-delta value because the building becomes more symmetrical and simpler.